Bioactive fraction from Lagerstroemia speciosa leaves (DLBS3733) reduces fat droplet by inhibiting adipogenesis and lipogenesis - Karsono AH; Tandrasasmita OM; Tjandrawinata RR (Dove Medical Press, 2019)
Agung Heru Karsono, Olivia Mayasari Tandrasasmita, Raymond Rubianto TjandrawinataSection of Molecular Pharmacology, Department of Research Innovation and Invention, Dexa Laboratories of Biomolecular Sciences, Dexa Medica, Cikarang, West Java, IndonesiaBackground: Obesity has become a risk factor for metabolic diseases. One of the cellular characteristics of obesity is the occurrence of adipose cells hyperplasia. Lagerstroemia speciosa is a plant which has been used for the treatment of diabetes. Furthermore, some studies also indicated that L. speciosa possesses antiobesity activity. Its antiobesity activity was examined in the present study through adipogenesis, lipogenesis, and lipolysis pathways.Aim: DLBS3733, a bioactive fraction of L. speciosa, was explored for its potential benefits to alter obesity through adipogenesis and lipogenesis inhibition and lipolysis induction activity.Materials and methods: This study was performed using 3T3-L1 cells. mRNA level and protein expressions related to adipogenesis, lipogenesis, and lipolysis pathways were assayed in this study.Results: Antiadipogenic effects of DLBS3733 (15 μg/mL) were found to be mediated by a significant downregulation of mRNA level of multicomponents involved in adipogenesis which include C/EBPα (CCAAT/enhancer-binding protein alpha) and PPAR-γ (peroxisome proliferator-activated receptor gamma) by 75% and 80.1% (p<0.05), respectively. DLBS3733 was found to inhibit lipogenesis, as shown by the significant reductions of adiponectin excretion and mRNA level of fatty acid synthase, SREBP (sterol regulatory element-binding protein), and ACC-β (Acetyl-CoA carboxylase) by 44.7%, 70.9%, and 83.1%, respectively (p<0.05). In addition, DLBS3733 was found to inhibit fat droplets accumulation in the cells in a dose-dependent manner through Oil-Red O staining. pAMPK protein was upregulated by 75% and ACC-β was downregulated by 88% (p<0.05) which indicates the reduction of lipid synthesis. Meanwhile, DLBS3733 showed an insignificant effect on adipose triglyceride lipase, hormone-sensitive lipase, and carnitine palmitoyl-CoA transferase-1 which indicate that DLBS3733 does not induce lipolysis.Conclusion: These results demonstrate the inhibitory activity of DLBS3733 on adipogenesis and lipogenesis. DLBS3733 may provide an effective and potential benefit in the prevention of obesity.Keywords: Lagerstroemia speciosa, obesity, adipogenesis, lipogenesis, adiponectin, ACC-β